EU Energy Policy: Difficulties in the Way of Implementation of Tasks - A. A. Abramova (Проблемы постсоветского пространства, 2024)
The article studies the problem of energy policy of the EU. Issues of creation of conditions necessary for realization of declared goals are considered. The features of implementation of the tasks are highlighted. It is concluded that the energy policy of the EU countries has both a number of advantages and a number of difficulties, which can become a significant obstacle to the implementation of all announced projects. The formation of European Union energy policy in recent years has been strongly influenced by external factors, such as: the emergence and development of new technologies, climate change, EU countries’ dependence on energy imports and new policy decisions. Considerable attention is being paid to renewable energy (RES) technologies, which, according to the official EU strategy, will be used for the construction of a closed energy system. Renewable energies include marine renewable energy, “green” public procurement, solar panels, alternative fuels. However, these projects pose a number of challenges for European countries, such as the need to build new infrastructure and reform the tax system. The fulfilment of all the objectives of the “European Green Deal” also involves certain risks, for example, the loss of a significant number of jobs by heavy industry workers and the loss of competitiveness of certain branches of the economy. European energy policy undoubtedly influences the policy of the Russian Federation. The global trend on renewable energy directly concerns Russia and the countries of the post-Soviet space, because this region has a high potential in this industry. This is particularly true for renewable energy sources such as wind power and hydropower. The development of renewable energy sources is undoubtedly a very important process for world politics, because energy is one of the most important resources that nations possess. It is very important to take this into account when considering the world’s political strategies.